Identify the Impact of Settlement on Agricultural Development in the Jordan Valley - Mostafa, Hisham Saleh (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to identify the impact of settlement on agricultural development in the Jordan Valley, to identify the reality of the agricultural sector in the Jordan Valley and its impact on the social situation and to analyze the impact of social, security and strategic settlement.The researcher used the descriptive approach on the theoretical aspect of the study, by studying the focus of the impact of the Israeli occupation on agricultural development in The Governorate of Jericho and the Jordan Valley.The study showed that Israeli settlement affects agricultural development in the Jericho and the Jordan Valley region and is the main obstacle to the development and growth of the agricultural sector. Long- term strategic plans for the development of the agricultural sector cannot be developed in the study area, and the absence of agricultural development in the study area will have a negative effect on the social, security and strategic situation.
Keywords: Israeli settlement; Jordan Valley; agricultural development